A SHORT REVIEW ON ASTAVARGA PLANTS- LOSING THEIR EXISTENCE - Rajashekhar, Ingalhalli; Hiren, Rathod; Hardik, Desai (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda is a rich source of Indian traditional knowledge governing the rules and regulations of living a healthy and long life. It preaches a disciplined way of good eating habits, physical activities and following their regular routine. Any indiscipline in observing these practices would lead to various health disorders and exhibit symptoms accordingly. In ancient times, Rishis and traditional healers/ Vaidyas thought about some plants as gifts of God which possessed divine power in their various parts and could treat any type of symptomatic disorders. Astavarga is a formulation developed from eight different plants by Ashwani Kumars to treat the frail and emaciated body of Rishi Chyavan. This formulation created the magic of rejuvenating Chyavan and since then is referred to as still famous Chyavanprash. These eight plants were selected from different ecological niches of Himalayas. Over a period of time, the availability of some of these eight plants has become scarce and manufacturers of his formulation are using substitutes which put a question mark on the efficacy of this wonder drug. An effort has been made in this article made to gather information from different sources about these plants and establish their current status which throws light on the measures to be taken to improve their status.